An AN ERROR ANALYSIS OF USING CONJUNCTION IN WRITING NARRATIVE TEXT (A Study at the First Grade Students of MTs YPKS Padangsidimpuan 2018/2019 Academic Year) - Nina Nurbaidah (Institut Pendidikan Tapanuli Selatan, 2019)
The aim of this research is to explain the quality of students’ writing in terms of conjunction and to analyze students’ problems using conjunction in writing narrative text. This research is a qualitative research method. This research also aim to know the causes of stuents’ problem using conjunction in writing narrative text. The writer chooses MTs YPKS Padangsidimpuan as the location of the research. The informant of this research are all of the students who comes from the seventh grade of MTs YPKS Padangsidimpuan. But, the writer only took one class to do this research that is VII-1.There are 30 students in this class and the writer only focus on 9 students. They have problems in using conjunction. The problems are related to the use of coordinating and subordinating conjunction. The reason of the problems in using conjunction in writing is based on linguistic, pragmatic, cognitive and cultural factor. Four of them give influence that causes the lack conjunction writing. Therefore, an intensive attention should be given by the lecture to facilitate the students to practice writing in the classroom and do peer correction.